Functional changes in the lower extremity after non-immersive virtual reality and physiotherapy following stroke - Pawel Kiper; Carlos Luque-Moreno; Salvatore Pernice; Lorenza Maistrello; Michela Agostini; Andrea Turolla (Medical Journals Sweden, 2020)
Objective: To analyse the effect of virtual reality (VR) ther-apy combined with conventional physiotherapy on balance, gait and motor functional disturbances, and to determine whether there is an influence on motor recovery in the subacute (< 6 months) or chronic (> 6 months) phases after stroke. Methods: A total of 59 stroke inpatients (mean age 60.3 years (standard deviation (SD) 14.8); 14.0 months (SD 25.7) post-stroke) were stratified into 2 groups: subacute (n  =  31) and chronic (n  =  28). Clinical scales (Fugl-Meyer lower extremity (FM LE); Functional Independence Measure (FIM); Berg Balance Scale (BBS); Functional Ambulation Category (FAC); modified Ashworth scale (MAS); 10-metre walk test (10MWT); and kinematic parameters during specific motor tasks in sitting and standing position (speed; time; jerk; spatial error; length) were applied before and after treatment. The VR treatment lasted for 15 sessions, 5 days/week, 1 h/day. Results: The subacute group underwent significant change in all variables, except MAS and length. The chronic group underwent significant improvement in clinical scales, except MAS and kinematics. Motor impairment improved in the severe < 19 FM LE points, moderate 20-28 FM LE points, mild > 29 FM LE points. Neither time since stroke onset nor affected hemisphere differed significantly between groups. The correlations were investigated between the clinical scales and the kinematic parameters of the whole sample. Moreover, FM LE, BBS, MAS, and speed showed high correlations (R2> 0.70) with independent variables. Conclusion: VR therapy combined with conventional physiotherapy can contribute to functional improvement in the subacute and chronic phases after stroke.